Simulation of atomic-force microscope contact mode operation taking into account nonmechanical forces of interaction with a specimen surface - Garishin, Oleg Konstantinovich (Computational Continuum Mechanics, 2012)
The discrete-mechanical model describing the interaction between the surface of a nonlinear-elastic polymeric material and the АFM cantilever of the atomic-force microscope (AFM) in the contact operation mode is proposed. The model takes into account not only the mechanical interaction between the AFM probe the material under study and but also the effect of van der Waals intermolecular force and the surface tension forces associated with the curvature of the specimen surface. Their influence on the general picture of interaction is found to be significant on the nano-scale level. The model consists of two sequentially joint spring-like elements. The first element (purely elastic) represents the mechanical effect of the АFМ cantilever. The second element is responsible for the mechanical response of the sample to intending of the AFM probe. The mechanical force is determined from the solution of a contact boundary-value problem. Analytical expressions for intermolecular and surface forces are obtained as the functions of the probe geometry and the distance between its apex and the sample surface.